Pancacuriga as a Tool for Analyzing Texts and Social Phenomena - Budi Setiawan Gardapandawa (Jomantara Indonesian Journal of Art and Culture, 2026)
Semiotics and discourse analysis serve as intellectual tools for exploring meaning beneath the surface, even unearthing the meaning behind the meaning. Meanwhile, Pancacuriga, also a "tool" for interpreting and understanding something, is more widely known and used by certain groups, such as puppeteers in wayang performances. Semiotics, discourse analysis, and Pancacuriga utilize a specific framework or structure for analysis. This paper examines Pancacuriga as a uniquely Indonesian analytical tool for reading texts and social phenomena. The method used is qualitative with a grounded theory design. Pancacuriga has a methodological cycle. The five elements of Sindir, Silib, Siloka, Simbul, and Sasmita form a communication system and simultaneously an epistemology—a uniquely Sundanese way of knowing and understanding. Pancacuriga, in essence, is the application of the scientific spirit to the humanities and social life. Semiotics, discourse analysis, and Pancacuriga are analytical systems that aim to uncover meaning beneath the surface, but differ in their origins, structure, and philosophical foundations.